Detection of Vt1 and Vt2 Genes in E. Coli O157:H7 Isolated from Soft Cheese in Basrah, Iraq Using Duplex Pcr - ABBAS, BASIL ABDULZAHRA; KHUDOR, MOHAMMED HASAN (Science Journal of University of Zakho, 2013)
During the period extended from November 2010 to March 2011, One hundred fifty soft cheese samples were collected from three different markets in Basrah city.  All samples were cultured in selective media to detect the presence of non-sorbitol fermenting colonies (NSF). 94 (62.66%) isolates were found non-sorbitol fermenting E. coli. Latex agglutination test was used to detect serotype O157:H7 in non- sorbitol fermenting isolates for 15 (33.34%) isolates. Duplex PCR were done to all E. coli O157:H7 isolates and the result showed 5/150 (3.34%) were positive to this test. All the E. coli O157:H7 isolates were positive to vt1 gene which was observed in 100% of isolates but none of the isolates were detected to having a vt2 gene.
Keywords: E. coli; duplex PCR; VT genes; Basrah